3D characterization of sand particle-to-particle contact and morphology. (April 2016) - Druckrey, Andrew M.; Alshibli, Khalid A.; Al-Raoush, Riyadh I.
Abstract: Particle morphology, orientation, and contact configuration play a significant role in the engineering properties of granular materials. Accurate three-dimensional (3D) characterization of these parameters for experiments has historically proven difficult, especially in the context of particle contact with small particle size. This paper describes a computer code that was developed to analyze 3D images of granular materials to measure particle lengths (size), volume, surface area, global centroid location and orientation; it also provides a method to calculate particle contact location and orientation. Measurements from the proposed code can define a state of the granular material's fabric that can be used as input for micro-mechanics based constitutive models and to validate numerical discrete element simulations. A fabric tensor and its evolution is calculated based on experimental contact normal vectors that were extracted from SMT imaging of an axisymmetric triaxial compression experiment on a natural silica sand known as F-35 sand.